Experimental and Numerical Analyses of a Spark-Ignition Engine Firing with N-Butanol-Gasoline Blends at High Load Operation. (August 2018) - Galloni, E.; Fontana, G.; Scala, F.
Abstract: In this paper, the potential of alcohol-gasoline blends as fuels for spark-ignition engines has been evaluated. The general purpose of the work is to verify the possibility of incrementing the bio-fuels penetration in the market of transportation fuels. As it is well known, bio-mass derived fuels, in fact, could significantly reduce the CO2 emissions of energy thermal systems. The behavior of a small, turbocharged spark-ignition engine, firing with gasoline-butanol blends, has been analyzed. Analyses have been carried out by means of both experimental tests and numerical simulations. In previous works, engine main performances have been illustrated and discussed. Here, experimental tests have been carried out in order to compare the engine knock resistance and the obtainable fuel conversion efficiency when the engine is fueled by pure gasoline or gasoline-butanol blends at high load operation. Furthermore, one dimensional numerical analyses have been utilized in order to compare the engine behavior, at different operating points, when it is firing with pure gasoline or pure butanol. In general, the obtained results seem to indicate that butanol (produced by bio-masses) is a viable alternative to fossil fuels in the way of CO2 emission reduction.